Augmenting the influence of the Chinese civilisation: the way of the Chinese dream - Vasilevskaya, Valeria E. (Journal of the Belarusian State University. International Relations, 2023)
The characteristics of China’s political system are examined with special attention to the details of the socio-economic development strategy declared by Xi Jinping in November 2012 and known as “Great revival of the Chinese nation – the Chinese dream”. The core of the strategy is explained from an analysis of China’s consistently changing political trajectory. It is demonstrated that a key element of the Chinese dream vision is the role of the state on the international stage.